Primary assessment of medicines for expected migrastatic potential with holographic incoherent quantitative phase imaging - Šuráňová, Markéta; Ďuriš, Miroslav; Štenglová Netíková, Irena; Brábek, Jan; Horák, Tomáš; Jůzová, Veronika; Chmelík, Radim; Veselý, Pavel (Biomedical optics express, 2023)
Solid tumor metastases cause most cancer-related deaths. The prevention of their occurrence misses suitable anti-metastases medicines newly labeled as migrastatics. The first indication of migrastatics potential is based on an inhibition of in vitro enhanced migration of tumor cell lines. Therefore, we decided to develop a rapid test for qualifying the expected migrastatic potential of some drugs for repurposing. The chosen Q-PHASE holographic microscope provides reliable multifield time-lapse recording and simultaneous analysis of the cell morphology, migration, and growth. The results of the pilot assessment of the migrastatic potential exerted by the chosen medicines on selected cell lines are presented.